Pemanfaatan Canva sebagai Media Pembelajaran Materi Menulis Puisi Kelas VIII - Ramadhani, Wahyu Wicaksono; Nasrullah, Riki (Universitas Muhammadiyah Magelang, 2026)
This study aims to describe the use of the Canva platform as a medium for Indonesian language learning in poetry writing skills for grade VIII students of SMP Negeri 34 Surabaya, including the form of Canva's use in learning, learning planning by educators, and student involvement and responses. This study uses a qualitative descriptive approach. The research subjects consisted of one Indonesian language teacher and twenty-seven grade VIII students. Data were collected through observation, directed interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions with data validity tests using method triangulation. The results of the study indicate that Canva is used as a learning medium from the planning stage, material delivery, to giving project-based assignments. The use of Canva can help visualize poetry material, stimulate imagination, and increase student activity and creativity in writing poetry. However, obstacles such as dependence on the internet network and potential design uniformity are still found. Overall, Canva plays a role as an innovative and relevant learning medium in teaching poetry writing skills at SMP Negeri 34 Surabaya.